2015
DOI: 10.1113/ep085063
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of hyperthyroidism on the stunned rat heart during ischaemia–reperfusion: energetics and role of mitochondria

Abstract: New Findings r What is the central question of this study?Hyperthyroidism is a cardiac risk factor, but thyroid therapy is used on myocardial stunning. What is the consequence of hyperthyroidism for mitochondrial metabolism and Ca 2+handling of the postischaemic stunned heart? r What is the main finding and its importance?Hyperthyroidism reduced stunning and improved muscle economy of the postischaemic rat heart. The activities of the mitochondrial sodium-calcium exchanger and mitochondrial K + channel in hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 57 publications
5
29
0
Order By: Relevance
“…Results suggest that the mNCX inhibition increases the mitochondrial Ca 2+ ‐dependent metabolism and the associated Ht (P/Ht falls) while reduces the cytosolic Ca 2+ and consequently the ∆LVEDP, in agreement to that suggested for these selective drugs . We have found that Clzp increased PICR in guinea‐pig hearts and in rat hearts exposed to no‐flow ischaemia. Results suggest that mitochondria contribute to the stunning because under LFI the mitochondria may be losing Ca 2+ through the mNCX.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Results suggest that the mNCX inhibition increases the mitochondrial Ca 2+ ‐dependent metabolism and the associated Ht (P/Ht falls) while reduces the cytosolic Ca 2+ and consequently the ∆LVEDP, in agreement to that suggested for these selective drugs . We have found that Clzp increased PICR in guinea‐pig hearts and in rat hearts exposed to no‐flow ischaemia. Results suggest that mitochondria contribute to the stunning because under LFI the mitochondria may be losing Ca 2+ through the mNCX.…”
Section: Discussionsupporting
confidence: 87%
“…Results suggested that blockade of mitochondrial Ca 2+ uptake through the UCam with Ru360 reduced P during both LFI and R in FH, with a fall in muscle economy during the hypoperfusion (Figure ). On this model, P was less affected than in a model of rat hearts exposed to no‐flow ischaemia and R with the same degree of stunning, in which Ru360 reduced PICR from about 75–20% . It was also reported that Ru360 reduced the rise in [Ca 2+ ]m suffered by rabbit cardyomyocytes under simulated I/R .…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations